VK’s Influence on Territorial Identity Formation in the Moscow Agglomeration / Фактор влияния социальной сети «ВКонтакте» на формирование территориальной идентичности жителей Московской агломерации - OLGA V. POPOVA / ПОПОВА О.В. (Наука телевидения)
There is a certain “blind spot” in the agglomeration development policy that is not obvious to managers, who mainly focus on economic potential. It is the cultivation of territorial identity, which allows people—even those who have arrived in the agglomeration not long ago and primarily see it as an opportunity to solve their financial issues or a springboard for their fur-ther careers—to sense the locality as a homeland, as their “own land”. Existing identity-building initiatives concentrate on the city and neighborhood levels. Studies of open online communication on social networks is an important source for assessing resident engagement with these politics, regardless of who initiated them: governmental or non-governmental actors, or residents themselves. Analysis of thematic focus, activity levels, and sentiment related to discussing identity politics projects and events within VKontakte groups representing Moscow agglomeration communities yielded positive results. Employing Big Data techniques, the study identified twelve key event types effectively promoting territorial identity on the city level, as well as neighbor-hood level, fostering a sense of shared belonging to both the locality and its community. Ranking various aspects of online discussions surrounding the implemented projects reveals which types of events deserve greater govern-mental attention for maximizing their impact on public perception.